Хашаат цавын хүрэн нүүрсний ордын геологийн тогтоц - А.Эрдэнэ; Б.Эрдэнэцогт (Geological Issues, 2023)
In this paper, the geological setting and coal quality of newly discovered brown (lignite) coal deposit. Khashaat Tsav. are summarized. The coal deposit is located in 82 km southeast of the center of Domed aimag, Mongolia and is discovered as a result of exploration program, conducted in 2014. Five coal seams with the thickness of 0.31 m to 42.62 m are hosted in Lower Cretaceous Aduunchuluun Formation. Coal measures form syncline structure and dip is up to 10 degree. According to lab analysis available so far, coal quality indices are shown in average as follows: moisture content (W, ar basis) - 36.99 %, ash content (A, ad basis) - 15.41 %, volatile matter (V, daf basis) 46.99 %, calorific values (Q, ar basis) - 3393kcal/kg and total sulfur content (S, ad basis) - 1.21 %. Also based on the results of drilling program, the coal reserve of the deposit is estimated to be 465 Mt, of which 94% is proven (A category) and probable (B category) reserves.